Securitization: From risk management to financial instability - SBIHI , Djamila; Chabha, BOUZAR (Dirassat Journal Economic Issue, 2016)
Since the subprime crisis of summer 2007, the virtues of securitization have been called into question. This technique, which is designed to secure other sources of finance for banks and transfer risks to other investors capable of managing them, has been the subject of several criticisms. It is considered to be the amplifying vector of the subprime crisis which deeply agitated the international financial markets causing a crisis of liquidity and confidence whose consequences were heavy. The crisis has exposed certain weaknesses and shortcomings from which securitization suffers, particularly in terms of the complexity of its set-up, the underestimation of risk by rating agencies by assigning ratings that do not reflect the reality of the risks inherent in the products of securitization, and also the presence of information asymmetry upon signing the contract. The purpose of this paper is to highlight the benefits of securitization, particularly in terms of risk management, which is considered to be one of the major concerns when it is implemented alongside the refinancing objective. It is also about trying to interpret its role in the triggering and the proliferation of the subprime crisis.